Towards codes of practice for navigating the academic peer review process. (July 2022) - Sovacool, Benjamin K.; Axsen, Jonn; Delina, Laurence L.; Boudet, Hilary Schaffer; Rai, Varun; Sidortsov, Roman; Churchill, Sefa Awaworyi; Jenkins, Kirsten E.H.; Galvin, Ray
Abstract: Peer review is the bedrock of modern academic research and its lasting contributions to science and society. And yet, reviewers can submit "poor" peer review reports, authors can blatantly ignore referee advice, and editors can contravene and undermine the peer review process itself. In this paper, we, the Editors of Energy Research & Social Science (ER&SS), seek to establish peer review codes of practice for the general energy and social science research community. We include suggestions for three of the most important roles: peer reviewers or referees, editors, and authors. We base our 33 recommendations on a collective 60 years of editorial experience at ER&SS . Our hope is that such codes of practice can enable the academic community to navigate the peer review process more effectively, more meaningfully, and more efficiently.